2003
DOI: 10.4031/002533203787536998
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Effects of Seismic Surveys on Marine Mammals

Abstract: This review highlights significant gaps in our knowledge of the effects of seismic air gun noise on marine mammals. Although the characteristics of the seismic signal at different ranges and depths and at higher frequencies are poorly understood, and there are often insufficient data to identify the appropriate acoustic propagation models to apply in particular conditions, these uncertainties are modest compared with those associated with biological factors. Potential biological effects of air gun noise inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
1
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(151 citation statements)
references
References 65 publications
(56 reference statements)
1
141
1
8
Order By: Relevance
“…Although relatively uncommon, incidental catches of small cetaceans in long-lines have been recorded in northeastern Brazil (Siciliano, 1994). Even though some authors reported negative effects of seismic activities on dolphins (Finneran et al, 2002;Gordon et al, 2003), our results do not allow further comments about this topic. …”
contrasting
confidence: 87%
“…Although relatively uncommon, incidental catches of small cetaceans in long-lines have been recorded in northeastern Brazil (Siciliano, 1994). Even though some authors reported negative effects of seismic activities on dolphins (Finneran et al, 2002;Gordon et al, 2003), our results do not allow further comments about this topic. …”
contrasting
confidence: 87%
“…This range is usually estimated from the maximum allowable exposure level using the backcalculated, broadband, on-axis source level of the airgun array. Most allowable range estimates also assume a geometric spreading transmission loss or a range-independent acoustic model with an omnidirectional sound source (Barlow and Gentry, 2004;Gordon et al, 2004). Since most airgun array source levels are calculated only on-axis and for frequencies below 250 Hz (Gausland, 2000), the range estimation described above does not account for the full frequency range produced by the array or the directionality of the array [although some regulatory approaches include a correction for array beampattern effects (NMFS, 2003)].…”
Section: Discussionmentioning
confidence: 99%
“…Even so, many research papers (e.g., Mohl et al, 2003; Au et al, 2004; Madsen et al, 2004; Mooney et al, 2004) and management protocols (e.g., National Marine Fisheries Service, 2003; Barlow and Gentry, 2004;Gordon et al, 2004) continue to use highly simplified descriptions of acoustic propagation without verifying their validity (either to simplify calculations, because they wish to present results relevant to a generic rather than a particular location, or because data on the environmental characteristics (required for more detailed models) was unavailable). In some cases, as detailed in Chapters 3-4 of this thesis, failing to model acoustic propagation realistically can lead to large errors in estimates of animal detection ranges or noise exposure levels.…”
Section: Implications Of Ocean Sound Propagation For Marine Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that noise emitted by seismic survey air-guns causes differing effects on different species of cetaceans due to: hearing sensitivity, behavior, habituation or desensitization, age, sex, location of exposure, and proximity to a shoreline (e.g. , Evans et al 1993, Gordon et al 2004, Madsen et al 2002. Recently, a study off Scotland has suggested that the absence of certain whale species from one sea area surveyed in 1998, where they might be expected to have been found, may have resulted from the incidence of seismic survey work there, although other potentially confounding variables are also noted (MacLeod et al, in press).…”
Section: Introductionmentioning
confidence: 99%